MAMA GUFRON: ANTARA VIRALITAS, SANAD KEILMUAN YANG RAGU, DAN SIKAP MUI TERHADAP DAKWAH NYELENEH - Yudo Handoko; Auren Bebyrahmadhani; Bunga Permatasari; Samia Ramadhani; Ledya Meiza Putri; Raissa Al Fitri; Jesyifa Azzahra Putri; Muhd Alfisyahri Wibowo (STKIP Subang, 2026)
The development of digital technology and social media has significantly transformed the practice of Islamic da'wah in Indonesia. This study examines the phenomenon of Mama Gufron (Ghufron Al-Bantani), a preacher who went viral in 2024 due to controversial claims such as communicating with angels via video call and speaking the 'language of ants.' Using a qualitative descriptive approach, this research analyzes how digital culture and popular culture influence the spread of religious messages and the shift in religious authority in the digital era. The findings show that the virality of Mama Gufron's phenomenon was driven by the unique and sensational nature of the content, the role of social media algorithms, meme culture, and public debate. This phenomenon reflects the challenges of maintaining the authenticity and depth of Islamic teachings amidst the rapid flow of digital popular culture. The study concludes that improving digital and religious literacy is essential for the public to critically filter religious information circulating on social media.